(untitled) (Aporte Santiaguino, 2019)
Existing the need to obtain fresh water for human consumption for the benefit of livestock associations located within the boundaries of the Sechura desert and the San Juan Bautista de Catacaos Peasant Community, in Piura, an experimental scientific study was carried out with the main objective compare different models of solar distillers, for at least 3 months, using brackish water from the artisanal well of farmers in the Tabanco sector. (with a 95% confidence interval) In order to determine the design of the best suitable freshwater solar distiller, from the point of view, environmental and economic, the research applied the Bifactorial statistical model of Random Blocks and did the analysis of variance that was complemented with the Tukey test; obtaining as a result that the solar distiller of two slopes is the most suitable design for the environmental conditions of the northern desert allowing a production of 1,509 to 1,767 liters of water per day/m2 of water mirror, for the evaluation period of the months of November to December, it is also the most economical, with a lower cost of 34.1 soles over a 10-year horizon to have 20 liters of distilled water per day